"Survival Mode": Rebel Resilience and the Lord's Resistance Army. Issue 5 (3rd September 2019) - Day, Christopher R.
ABSTRACT: To date, scholarly work on armed groups has seldom considered the notion of rebel resilience, or the factors that enable these groups to survive despite time, military pressure, and the myriad contingent events of civil war. In an effort to develop an explanatory framework for resilience as a distinct outcome of civil war and rebellion, this article examines the conditions under which the Lord's Resistance Army (LRA) has persisted for nearly three decades. Based on fieldwork and original research, the article explains the LRA's resilience in light of the group's organizational structure and resource self-sufficiency, which have been well suited for the borderlands of East and Central Africa. The LRA is a key case of rebel resilience. It is important because it sheds light on the organizational foundations of armed groups, the relationship between resources and rebellion, and the broader study of conflict duration and termination. Understanding the sources of the LRA's resilience can inform efforts to end such insurgencies.